EFFECTS OF CEMENT DUST ON THE HEMATOLOGICAL PARAMETERS IN OBAJANA CEMENT FACTORY WORKERS - Emmanuel, T.F.; Ibiam, U.A.; Okaka, A.N.C.; Alabi, O.J. (European Scientific Journal, ESJ, 2015)
This study investigated effects of cement dust on haematological parameters of Obajana Cement factory workers. The investigation of haematological parameters were performed on 60 workers in different units/sections exposed to cement dust and controls (unexposed to cement dust). Automated Abascus Haematoanalyser was used to analyse haematological indices. The results showed that the values of white blood cell (WBC), lymphocytes (LYM), monocytes (MID), haematocrit (HCT), mean corpuscular haemoglobin (MCH), mean corpuscular heamoglobin concentration (MCHC) and platelets (PLT) were significantly increased in exposed workers but red blood cell (RBC) and Haemoglobin (HGB) were significantly lower( p < 0.05). Results also showed a long term duration response effect on the Haematological indices in relation to years and age of workers of exposed to cement dust. In this study alteration in level of haemotological parameters in exposed workers is an indication of effect of cement dust on pathopysiology of blood and reticuloendothelia system of cement factory workers and in general human health. This study highlighted the need for continuous cement dust environmental monitoring, mandatory use of personal protective equipment and periodic haematological assessment of factory workers to prevent related haematological hazard.